Simultaneously Good Stability and High Speed Based on Oxygen-Doped Zn15Sb85 Material. (1st January 2018) - Zhang, Rui; Hu, Yifeng; Zhu, Xiaoqin; Chou, Qingqian; Lai, Tianshu
Abstract : In this study, the amorphous-to-crystalline transitions of oxygen-doped Zn15 Sb85 materials were investigated by in situ film resistance measurements. After oxygen doping, the thermal stability, resistance and bandgap of the Zn15 Sb85 material increased significantly. The data retention temperature for 10 years increased from 58°C of pure Zn15 Sb85 to 200°C of oxygen-doped Zn15 Sb85 . The X-ray diffraction pattern showed that lots of Sb phases existed in O-doped Zn15 Sb85, which induced the fast phase change. The formation of some Zn and Sb oxides were confirmed by X-ray photoelectron spectroscopy. The surface morphology observed by atomic force microscopy demonstrated that oxygen doping refined the grain size and restrained the crystallization. An ultra-short switching time of 2.40 ns was achieved for oxygen-doped Zn15 Sb85 material. The results showed that appropriate oxygen doping could improve the performance of the Zn15 Sb85 material in phase change memory.